MASALAH KETERLAMBATAN PENANDATANGAN AJB DAN PENYERAHAN UNIT APARTEMEN REGATTA (STUDI PUTUSAN NO. 573/PDT.G/2020/PN JKT.UTR) - Sheira Maghfira Maulani Utami; Anda Setiawati (Fakultas Hukum Universitas Trisakti, 2021)
Marketing of flats before the construction is completed is done by many developers. Generally, marketing is preceded by a legal bond as outlined in the PPJB. In practice, many problems occur where developers do not fulfill their obligations as stated in the PPJB and as a result prospective buyers file a default lawsuit to the court. The formulation of the problem regarding whether the default lawsuit filed by prospective buyers of the Regatta Apartment is in accordance with applicable legal provisions and whether the judge's consideration in Decision No. 573/Pdt.G/2020/PN Jkt.Utr is in accordance with the provisions of the law. Normative juridical research method which is descriptive analytical and the conclusion is drawn inductively, secondary data (library data) only. The results of the research, discussion and conclusion are that the default lawsuit filed by the prospective buyer is appropriate because the developer's actions that violate Article 5.1 of the PPJB include acts of default. For the consideration of the judge who stated that the developer was in default in accordance with the provisions of the law because the developer was proven not to have carried out his obligations to make AJB in front of PPAT and to deliver Regatta apartment units to prospective buyers.